A study on information perception and engagement, emphasizing the essential role of E-clinics among Palestinian adolescents - Nour Issa; Maysaa Nemer; Niveen Abu-Rmeileh (PLoS ONE, 2025)
Adolescents increasingly rely on electronic platforms for health information, highlighting their rapid technological adoption among significant developmental changes. Utilizing E-clinics presents a promising approach to enhance their health outcomes. This study aimed to identify adolescents’ preferred health information sources, the challenges guiding their choices, and assess their willingness to use E-clinics. A cross-sectional survey was conducted among adolescents in grades 8–12 in governmental schools across the West Bank, Palestine. 646 questionnaires were distributed (69.5% females, 30.5% males; median age 16). Results highlighted family/friends (34.4%), HCPs (32.5%), and the Internet (23.7%) as primary sources of health information, with 91.2% of Internet users seeking health advice. Internet convenience (56.2%), abundant information (31.9%), and anonymity (7.6%) were valued by participants. Place of residence significantly (p < 0.001) influenced health information sources, with 94.4% in the center preferring the Internet. Three key factors emerged: trust in HCPs (p < 0.001) influenced reliance on them (76.7%), and willingness to use E-clinics for privacy (63.5%); distrust in healthcare services led to Internet reliance (32.7%) and E-clinic interest for privacy (30.4%); privacy concerns (p = 0.00) led unconcerned participants (52.9%) to rely on the Internet, and 51.6% believed E-clinics were private. Trust in HCPs and healthcare services influenced E-clinic anonymity perception, while location and privacy concerns affected E-clinic benefits perception. Findings suggest that E-clinics can improve accessibility to healthcare by filling the gaps left by traditional healthcare models while also addressing privacy issues. Incorporating them in healthcare systems that serve adolescents can improve trust, accessibility, and improve well-being.